Analisis Faktor Penggunaan Dompet Digital di Kalangan Mahasiswa Perguruan Tinggi Surabaya - Rafi Indra Permana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Nowadays, technological developments occur very rapidly. All areas of life also develop following technological developments. One of the areas that is growing rapidly and attracting a lot of attention is the financial area. One of the technological developments in finance or what is commonly referred to as Financial Technology incudes digital wallets. Digital Wallets are widely used by all levels of society, including students. This research was conducted to determine the factors of the use of digital wallets among students. This research was conducted by distributing questionnaires to college students in Surabaya. The results of the questionnaire were processed using descriptive statistics and conclusions were drawn from the data. The results obtained from this study are that students agree with the various factors of using digital wallets that have been mentioned by researchers in the questionnaire.